+0  
 
0
488
1
avatar

x^2+y^2+3x-2y-1=0 find the standard form

 Oct 29, 2017
 #1
avatar+95859 
+2

 

Rewrite as

 

x^2 + 3x + y^2 - 2y = 1

 

Complete the square on x and y

 

x^2 + 3x + 9/4 + y^2 - 2y + 1  =  1  + 9/4  + 1

 

( x + 3/2)^2  +  ( y - 1)^2  =  2 + 9/4

 

( x + 3/2)^2  +  ( y - 1)^2  =  8/4 + 9/4

 

( x + 3/2)^2  +  ( y - 1)^2  =  17/4 

 

 

cool cool cool

 Oct 29, 2017

23 Online Users

avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.